Rural tourism and sustainable business - Hall, C. Michael; Hall, Derek R; Hall, Derek; Kirkpatrick, Irene; Mitchell, Morag; Mitchell, Morag (Aspects of Tourism, 2005)
This book provides the latest conceptual thinking on, and case study exemplification of, rural tourism and sustainable business development from Europe, North America, Australasia, the Middle East and Japan in 19 concise, manageable chapters. The book is organised into distinct yet interrelated sections, and benefits from strong editorial input in terms of context setting and summary chapters. Rural Tourism and Sustainable Business represents a high quality text integrating the latest thinking on the evolving strategic roles of rural tourism and its role in sustainable business development. It provides readily accessible material drawn from a range of environmental and cultural contexts and draws attention to the nature and interrelationships between local and global issues in rural tourism and development.